1979
DOI: 10.1161/01.str.10.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemorrhagic hypotension on the cerebral circulation. II. Electrocortical function.

Abstract: SEVERE HYPOTENSION produces a loss of cerebral function, the extent and reversibility of which depends on the degree and duration of the period of hypotension. Recent studies have described the changes in cerebral function over periods of sustained hypotensionThe present study forms part of a systemic investigation which attempts to correlate the changes in cerebral blood flow during graded hemorrhagic hypotension with the subsequent alteration in cerebral functional activity and the development of hypoxic bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…23 Rather, they favor the hypothesis that various neuronal groups differ in their sensitivity to ischemia or hypoxia. 24 Our results showed a faster recovery of the EEG compared with the somatosensory-evoked potentials; these findings confirm the experience of other authors 12 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…23 Rather, they favor the hypothesis that various neuronal groups differ in their sensitivity to ischemia or hypoxia. 24 Our results showed a faster recovery of the EEG compared with the somatosensory-evoked potentials; these findings confirm the experience of other authors 12 …”
Section: Discussionsupporting
confidence: 86%
“…To evaluate these contradictory findings, we tested the effect of lidocaine by using a moderate level of blood flow reduction defined by changes in the electroencephalogram (EEG) comparable with those studied by Gregory et al 12 and Graham et al, 13 who reported no neuropathologic alterations after 20 minutes of incomplete global ischemia. We tested a low dose of the drug, expecting some central nervous system beneficial action because lidocaine has a significant effect at low concentrations in other excitable tissue; one of these effects is the suppression of cardiac arrhythmias.…”
mentioning
confidence: 99%
“…Such mechanisms and relationships have not previously been described systematically. In the accompanying communications, the vascular mechanisms will be related to changes in electrocortical function, 2 and to the development of neuropathological changes in the cerebral parenchyma. …”
Section: Stroke Vol 10 No 6 1979mentioning
confidence: 99%
“…Branston and co-workers used a combination of middle cerebral artery occlusion and hypotension, while we only use general hypotension. On the other hand, Gregory et al (1979) also used only hypotension and found a threshold for transmission failure at a slightly higher flow than Branston and co-workers, i. e. , when CBF had decreased to about 50% of control.…”
Section: Discussionmentioning
confidence: 89%